Happy birthday, Addy! : a springtime story - Porter, Connie Rose, 1959-; Smith, Luann Roberts; Brown, Bradford (Middleton, WI : Pleasant Co., 1994)
Trying to shape a new life of freedom in Philadelphia after having been a slave, Addy finds inspiration from a new friend.
Keywords: Afro-Americans -- Fiction; Fugitive slaves -- Fiction